CHALLENGES AND CIRCUMSTANCES OF MEDIUM SIZE ENTERPRISES EMPLOYEES WORK LIFE BALANCE - Dhas, D. Babin; S. C. Vetrivel (International Journal of Psychosocial Rehabilitation, 2020)
The analysis of the problem of work- life balance (WLB) expanded through the last few years, being transformed and connected with family life, into more general issue, concerning all the employees. The problem occurs especially with reference to the Medium Size Enterprises, which dominate in the enterprise structure in the world. At the same time these organizations represent relatively low standards in terms of realization of the basic rules of HR management, including WLB. It is caused not only by the system and organizational limitations, but it is also a result of a lack of the employers’ awareness in relation with a given area. It also seems to be interesting that the peculiarity of the functioning of a SMEs may be recognized as a factor fostering efficient management of WLB (greater flexibility in decision- making process, greater flexibility in terms of structural and economic matters), but at the same time size of the company can be recognized as a factor creating an obstacles in implementation of the WLB idea (ad hoc management, lack of knowledge in the area of shaping activities concerning WLB, focus on profit in a short time, lack of strategic management, lack of formal representations of the employees’ interests). The aim of the article is to present the results of authors’ own research focusing on the Circumstances of WLB of SME’s employees.